The Application of Storytelling in Learning Aqidah Akhlak about Prophet Ibrahim AS - Komarudin, Asep (International Journal Labs, 2021)
The application of the storytelling can be used as an alternative learning method used, especially in learning Aqidah Akhlak, with this method besides being able to quickly hit the hearts of students it is also not easy to get bored because through storytelling students can take ibrah from the stories of the Prophets, to be applied in everyday life. The problem is how the storytelling can be applied effectively so that the implementation of Aqidah Akhlak learning gets a positive response, attracts attention, can be developed and practiced in everyday life. The objectives of this research are to find out the application of the storytelling in learning Aqidah Akhlak material about the story of Prophet Ibrahim AS at MDTA Riyadlut Ta'limiyyah and the effectiveness of the Storytelling in learning Aqidah Akhlak the material for the story of the Prophet Ibrahim AS at MDTA Riyadlut Ta'limiyyah. This study uses a qualitative descriptive approach, namely research in which the data is in the form of words and the source comes from interviews, report notes, documents and others. The results showed that the application of the Storytelling in learning Aqidah Akhlak at MDTA Riyadlut Ta'limiyyah was relatively effective. As evidence that the learning process is effective, the enthusiasm of students during the learning process, student activity and evaluation results are increasing.